KENDALI OPTIMAL PADA MODEL DINAMIK EPIDEMI DENGUE MENGGUNAKAN MISER3 - Leleury, Zeth A. (PATTIMURA UNIVERSITY, 2012)
Dengue fever is an infectious tropical disease caused by the Dengue virus. Dengue haemorrhagic fever constitute a substantial health burden on world's population. In thisresearch, an application of optimal control theory to Dengue epidemics using MISER3 was presented. The dynamic model is described by a set of nonlinear ordinary differentialequations, that depend on the dynamics of the Dengue mosquito, the number of infected individuals, and people's motivation to combat the mosquito. The cost functional dependsnot only on the costs of medical treatment of the infected people but also on the costs related to educational and sanitation campaigns. We observe that with currentcomputational tools it is easy to obtain, in an efficient way, better solutions to Dengue problems, leading to a decrease in the number of infected mosquitoes and individuals inless time and with lower costs.